Bridging Tradition and Innovation: English Language Teaching Methodologies at IAI Al-Aziziyah - Firman, Firman; Samad, Iskandar Abdul; Muthalib, Kismullah Abdul (Universitas Pendidikan Ganesha, 2025)
This study explores English Language Teaching (ELT) methodologies at IAI Al-Aziziyah Islamic Institution, addressing the methods used, adherence to pedagogical criteria, and challenges in implementation. Employing a qualitative case study design with in-depth interviews involving four lecturers, the research revealed significant reliance on traditional approaches, particularly the Grammar-Translation Method (GTM), for teaching grammar and vocabulary. While contemporary methodologies like Communicative Language Teaching (CLT) and Content-Based Instruction (CBI) were adopted to some extent, their inconsistent application highlighted limitations, including inadequate use of real-life contexts and collaborative tasks. Minimal application of Task-Based Learning (TBL) and Total Physical Response (TPR) further reflected a gap between theoretical ideals and practice. Challenges such as large class sizes, limited teaching resources, and the complexity of integrating Islamic values into ELT were prominent. The findings emphasize the need for professional development, enhanced institutional support, and culturally adaptive teaching methods to improve ELT outcomes in the Aceh context. This study underscores the importance of aligning ELT methodologies with local cultural and religious values while fostering communicative competence and active learning. Future research should investigate innovative strategies for integrating Islamic perspectives into ELT practices.